America Y2K: The Obsolescence of Educational Reforms - Dorn, Sherman (Education Policy Analysis Archives, 2000)
The passing of the deadline for fulfillment of the national education goals in the United States (the beginning of 2000) reflects the frequently hyperbolic statements of objectives and the manic pace of school reform efforts over the past two decades. The domination by schools of child and family life has combined with a longstanding reliance on schools to solve social problems to make school reform a politically opportune as well as visible issue. Thus, even if the phrasing of national education goals in the U.S. changes to reflect the passing of the nominal deadline, those pressures will remain.